Evaluation the Serum Levels of ADAMTS-13 among Iraqi Patients with Hypertension - Hamed, Suhad Mohammad (American Journal of Biology and Natural Sciences, 2024)
Hypertension is a major public health problem due to its high prevalence all around the globe. Adisentgrine and metallopeptedase with thrombospondin type1 motif13 (ADAMTS-13), which encodes a metalloproteinase responsible for cleaving von Willebrand factor (VWF), a key player in platelet adhesion and aggregation. The identification of specific ADAMTS-13 gene polymorphisms associated with hypertension could lead to the development of genetic biomarkers for risk stratification. The aim of this to evaluate serum levels of ADAMTS-13 in patients with hypertension in an Iraqi population. Forty five hypertensive patients (23 males and 22 females), their age 40-70 years and 35 healthy controls (18 males and 17 females), their age range between 40-70 years. were selected from Wasit Province using a convenient sampling method.Serum levels of ADAMTS-13 was performed using by enzyme-linked immunosorbent assay technique (ELISA) using Human- ADAMTS-13kit. In patients and controls. The results of serum levels of ADAMTS-13 reveal highly significant differences, the ADAMTS-13 levels in sera from hypertensive patients were higher than that of controls (1553.69598+467.80990), controls (318.31783+9.39208), P=0.0227. It is noteworthy that the ADAMTS-13 levels in the current study were lower significantly among males and females patients withe hypertension compared with control group ,(1038.87133±231.08107) versus (337.86575± 15.83530) P=0.0001,(1855.16940±529.36715 versus (387.01973±64.50541) P=0.0002 respectively . ADAMTS-13 levels revealed non-significant difference when comparing male patients with female patients 1038.87133±231.08107 versus 1855.16940± 529.36715 with a non-significant difference P=0.1713. Based on the polymorphism of,serum (ADAMTS13) rs28503257 A/G levels of ADAMTS-13 showed that hypertensive patients with homozygous AA genotype appeared non-significant difference when compared with the healthy individuals with AAgenotype 2340.73550±421.37615 vs. 441.50058±111.61452,P= 0.0001.The patients carrying the heterozygous AG genotype revealed significant decline in ADAMTS-13 serum levels 1820.89450±180.06750 in comparison with controls carrying this genotype 340.87340±9.62072,P=0.0001. These results are in agreement with the results of association analysis which demonstrate that these genotypes represents the most ones predisposed to hypertension.In conclusion, Serum levels of ADAMTS-13 are significantly correlated with hypertension and may reflect the role of ADAMTS-13 in the pathogenesis of the diseases.